Effects of rosmarinic acid on DNA integrity and H19 differentially methylated region methylation levels in human sperm preserved by freeze-drying - Yi-Yu Wang (Reproductive and Developmental Medicine, 2021)
Objective: To investigate the effects of rosmarinic acid (RA) on the DNA integrity and methylation levels of the H19 differentially methylated region (DMR) of freeze-dried human sperm after 1 week and 6 months of storage at 4°C. Methods: Semen samples from 15 healthy normospermic donors were used in this study. The samples were divided into five groups, including the control group with fresh sperm and four experimental groups with freeze-dried sperm (1-week storage with EGTA buffer solution, Group A; 1-week storage with EGTA buffer solution containing 105 μmol/L RA, Group B; 6-month storage with EGTA buffer solution, Group C; and 6-month storage with EGTA buffer solution containing 105 μmol/L RA, Group D). DNA integrity was evaluated using the sperm chromatin dispersion test. H19 DMR methylation levels were detected by bisulfite sequencing polymerase chain reaction. Results: After 1 week of storage, no differences in sperm DNA integrity were observed among Groups A, B, and controls (P > 0.05). After 6 months of storage, the sperm DNA integrity of Group D did not change significantly compared with that of the control group (P > 0.05), whereas that of Group C decreased significantly (P < 0.05). There were no differences in H19 DMR methylation levels among the five groups (P > 0.05). Conclusions: The DNA integrity of freeze-dried human sperm can be effectively protected by adding RA within 6 months, and the H19 DMR methylation level of human sperm can be maintained for 6 months after freeze-drying.